Patient-Reported Outcomes in Clinical Trials Leading to Cancer Immunotherapy Drug Approvals From 2011 to 2018: A Systematic Review. (4th November 2020) - Safa, Houssein; Tamil, Monica; Spiess, Philippe E; Manley, Brandon; Pow-Sang, Julio; Gilbert, Scott M; Safa, Firas; Gonzalez, Brian D; Oswald, Laura B; Semaan, Adele; Diab, Adi; Chahoud, Jad
Abstract: Background: Patient-reported outcomes (PROs) promote patient centeredness in clinical trials; however, in the field of rapidly emerging and clinically impressive immunotherapy, data on PROs are limited. Methods: We systematically identified all immunotherapy approvals from 2011 through 2018 and assessed the analytic tools and reporting quality of associated PRO reports. For randomized clinical trials (RCTs), we developed a novel 24-point scoring scale: the PRO Endpoints Analysis Score based on 24 criteria derived from the recommendations of the Setting International Standards in Analyzing Patient-Reported Outcomes and Quality of Life Endpoints Data Consortium. Results: We assessed 44 trial publications supporting 42 immunotherapy approvals. PROs were published for 21 of the 44 (47.7%) trial publications. Twenty-three trials (52.3%) were RCTs and 21 (47.7%) pertained to single-arm trials. The median time between primary clinical outcomes publications and their corresponding secondary PRO publications was 19 months (interquartile range = 9-29 months). Of the 21 PRO reports, 4 (19.0%) reported a specific hypothesis, and most (85.7%) used descriptive statistics. Three (3 of 21 [14.3%]) studies performed a control for type I error. As for RCTs, 14 of 23 (60.9%) published PRO data, including 13 (56.5%) that published a secondary dedicated manuscript. One-half of these 14 trials scored less than 13 points on the 24-point PRO Endpoints Analysis Score. The mean score was 12.71 (range = 5-17, SD = 3.71), and none met all the recommendations of the Setting International Standards in Analyzing Patient-Reported Outcomes and Quality of Life Endpoints Data Consortium. Conclusions: Suboptimal reporting of PROs occurs regularly in cancer immunotherapy trials. Increased efforts are needed to maximize the value of these data in cancer immunotherapy development and approval.